2018
DOI: 10.1159/000484482
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Series Study of the Effect of Air Pollution on Outpatient Visits for Acne Vulgaris in Beijing

Abstract: Background/Aims: There is increasing evidence that exposure to air pollutants, including particulate matter (PM2.5, PM10), nitrogen dioxide (NO2), and sulfur dioxide (SO2), might aggravate preexisting skin diseases such as eczema and urticaria. Here we investigated if a possible link exists between air pollution and acne vulgaris. We assessed the association between ambient air pollutant concentrations and the number of visits of patients for acne vulgaris to a derma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 9 publications
(13 reference statements)
2
41
0
1
Order By: Relevance
“…recently reviewed three Asian studies that suggested a pollutant‐specific relationship between elevated levels of airborne pollutants and an increased prevalence of acne. Elevated levels of PM 2.5 , PM 10 and NO 2 were associated with an increase in the number of acne‐related outpatient visits to a dermatology clinic in Beijing . Pollutants were also listed as one of the acne exposome factors in a recent review by Dreno et al …”
Section: Pollutants and Inflammatory Skin Diseasesmentioning
confidence: 99%
“…recently reviewed three Asian studies that suggested a pollutant‐specific relationship between elevated levels of airborne pollutants and an increased prevalence of acne. Elevated levels of PM 2.5 , PM 10 and NO 2 were associated with an increase in the number of acne‐related outpatient visits to a dermatology clinic in Beijing . Pollutants were also listed as one of the acne exposome factors in a recent review by Dreno et al …”
Section: Pollutants and Inflammatory Skin Diseasesmentioning
confidence: 99%
“…However, these two studies did not compare the possible differences in facial signs (pigmented spots, wrinkles, sagging, vascular disorders…), linked to combined aging and photo‐aging processes, that could be UP‐related. Epidemiological studies, related to outdoor or indoor conditions, pinpoint UP as a triggering factor of some cutaneous disorders and skin aging .…”
Section: Introductionmentioning
confidence: 99%
“…Skin, as the first line to interface with the air, is the target of various environmental stressors (Valacchi et al, 2012;Dong et al, 2019). Basic and clinical studies have provided growing evidence that airborne pollutants exacerbate skin aging (Vierktter et al, 2010;Ding et al, 2017) and even some chronic inflammatory skin diseases (Ahn, 2014;Pesce et al, 2015;Liu et al, 2018), which also exists when there is microbiome imbalance (He et al, 2006;Nielsen and Jiang, 2019). However, whether airborne pollutants have an impact on microbial communities of healthy skin, especially facial microbiome, still needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that accumulation of SO 2 and NO x could result in a lower pH value of rainwater (Li et al, 2019), and difference of pH would further lead to composition change in local microbiota (Vongsa et al, 2019). Available evidence indicate that long-term air pollution could accelerate skin aging (Vierktter et al, 2010;Ding et al, 2017), and some human skin diseases, such as acne (Liu et al, 2018), atopic dermatitis (AD; Ahn, 2014), and eczema (Pesce et al, 2015), were also reported to be associated with dysbiosis of skin microbiota (Fitz-Gibbon et al, 2013;Chng et al, 2016;Dybboe et al, 2017;Shibagaki et al, 2017;Kim et al, 2019;Reiger et al, 2020). On the one hand, it was uncovered that exposure to atmospheric-equivalent O 3 levels for 2 h could halve the skin microbiome of women's forearm (He et al, 2006).…”
Section: Introductionmentioning
confidence: 99%